Social Utility of Academic Research - Mishra, Chaitanya (Himalayan Journal of Sociology and Anthropology, 2011)
The Nepal Intellectual Forum (NepIf), Pokhara, had invited Professor Chaitanya Mishra to deliver a lecture on ‘Social Utility of Academic Research’ on May 22, 2010. We thank Prof Mishra and the NepIf for providing extracts from the lecture to this publication. -Editors DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4678 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 241-253